KINERJA KARYAWAN DITINJAU DARI KEDISIPLINAN KOMPENSASI DAN INTEGRITAS PADA KANTOR KSPPS BMT SAKINAH SUKOHARJO - Sarsono; Fajar Sipanuh; Supawi Pawenang (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the effects of discipline, compensation, and integrity on employee performance at KSPPS BMT Sakinah Sukoharjo. The study employs a quantitative approach using multiple linear regression analysis. The population as well as the sample consists of all employees of KSPPS BMT Sakinah Sukoharjo, totaling 45 respondents. Data were collected through questionnaires that had been tested for validity and reliability. The results indicate that discipline, compensation, and integrity simultaneously have a positive and significant effect on employee performance. The coefficient of determination of 54.0% shows that the three independent variables are able to explain 54.0% of the variation in employee performance, while the remaining percentage is influenced by other factors outside the research model. These findings emphasize the importance of effective discipline management, fair compensation systems, and the strengthening of integrity values in improving employee performance in Islamic microfinance institutions Keywords: discipline, compensation, integrity, employee performance, KSPPS BM